Effects of increased temperature on arctic slimy sculpin Cottus cognatus is mediated by food availability: Implications for climate change. (19th December 2020) - Pennock, Casey A.; Budy, Phaedra; Atkinson, Carla L.; Barrett, Nick
Abstract: Lakes are vulnerable to climate change, and warming rates in the Arctic are faster than anywhere on Earth. Fishes are sensitive to changing temperatures, which directly control physiological processes. Food availability should partly dictate responses to climate change because energetic demands change with temperature, but few studies have simultaneously examined temperature and food availability. We used a fully factorial experiment to test effects of food availability and temperature (7.6, 12.7, and 17.4°C; 50 days) on growth, consumption, respiration, and excretion, and effects of temperature (12 and 19.3°C; 27 days) on habitat use and growth of a common, but understudied, mid‐level consumer, slimy sculpin Cottus cognatus, in arctic lakes. We also used bioenergetics modelling to predict consumptive demand under future warming scenarios. Growth rates were 3.4× higher at 12.7°C in high food compared to low food treatments, but the magnitude of differences depended on temperature. Within low food treatments, there was no statistical difference in growth rates among temperatures, suggesting food limitation. Consumption, respiration, and nitrogen excretion increased with temperature independent of food availability. Lower growth rates coincided with lower phosphorus excretion at the highest temperature, suggesting that fish selectively retained phosphorus at high temperatures and low food. In habitat choice experiments, fish were more likely to use the 12°C side of the tank, closely matching their optimal temperature. We predicted a 9% increase in consumption is required to maintain observed growth under a 4°C warming scenario. These results highlight considering changes in food resources and other associated indirect effects (e.g. excretion) that accompany changing temperatures with climate change. Depending on how food webs respond to warming, fish may cope with predicted warming if density‐dependent feedback maintains population sizes.